A cross sectional study to assess the knowledge, attitude and practice towards road traffic safety among adolescent students of a selected Pre-University college in Raichur city - Ranjan, Din Prakash; Fahim, M. A.; Kirte, Rahul C. (International Journal Of Community Medicine And Public Health, 2018)
Background: Globally, road traffic injuries are estimated to be the leading cause of death among young people aged 15–29 years, and second leading cause of death in 10–14 years and 20–24 years age groups. The objective of the study is to assess the knowledge, attitude and practice towards road traffic safety among adolescent students of a selected Pre-University college in Raichur city. Methods: Cross-sectional study conducted among (372) adolescent students of a selected Pre-University college in Raichur city by using pre-tested, semi-structured questionnaire and analyzed using Epi-Info software. Chi-Square test was applied and level of significance was kept at P value of <0.05. Results: Mean age of the participants was 16.68±0.75. 196 participants (52.8%) had adequate knowledge on the road safety rules and regulations. Only 25 participants (7.7%) were driving with a valid driving license. The most common reason for motor vehicle accidents was high speed. Knowledge adequacy about road safety rules and regulations had statistically significant association with age and gender. Conclusions: Mere knowledge does not necessarily translate into improved traffic behavior as was seen in this study. School/college is the basic institution where we can formulate interventions. Continuous reinforcement and education reminding them of traffic rules can bring about a positive change and motivate them to strictly adhere to the traffic norms and help reduce the morbidity and mortality regarding road traffic accidents.